2009
DOI: 10.1126/science.1176980
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Polymorphism to Interspecific Divergence: Genetics of Pigmentation in Drosophila

Abstract: Genetic changes contributing to phenotypic differences within or between species have been identified for a handful of traits, but the relationship between alleles underlying intraspecific polymorphism and interspecific divergence is largely unknown. We found that noncoding changes in the tan gene, as well as changes linked to the ebony gene, contribute to pigmentation divergence between closely related Drosophila species. Moreover, we found that alleles linked to tan and ebony fixed in one Drosophila species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
162
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(174 citation statements)
references
References 23 publications
10
162
1
Order By: Relevance
“…In contrast, in Drosophila, alterations in the spatial expression patterns of a small set of melanin synthesis genes, such as yellow, tan and ebony, causes species-specific variations in colour patterns; the expression control of tan and yellow is involved in the divergence of abdominal pigmentation between D. santomea and D. yakuba 49,50 . In addition, these few melanin-related genes have been reported to be involved in pigmentation diversity in several Drosophila species 22,51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in Drosophila, alterations in the spatial expression patterns of a small set of melanin synthesis genes, such as yellow, tan and ebony, causes species-specific variations in colour patterns; the expression control of tan and yellow is involved in the divergence of abdominal pigmentation between D. santomea and D. yakuba 49,50 . In addition, these few melanin-related genes have been reported to be involved in pigmentation diversity in several Drosophila species 22,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most convincing data for the genetic and evolutionary control of colour patterns were obtained from different species or spontaneous mutants within species of Drosophila and some butterflies [12][13][14][15][16][17][18][19][20][21][22] . In those reports, various genetic changes that contributed to phenotypic differences within or between species were identified; however, the phenomena by which a single locus (gene) can produce multiple phenotypic traits are largely unknown 22 . Because genetic polymorphisms underlie the convergent and divergent evolution of colour pattern diversity 23 , identifying the essential gene that controls this phenotypic diversity is of great interest.…”
mentioning
confidence: 99%
“…Genetic and candidate gene studies have revealed some pleiotropic genes involved in the formation of diverse pigmentation patterns on the wings and bodies of butterflies [1][2][3] and Drosophila 4-7 -patterns that are important in processes such as mimicry 3,8,9 , geographical adaptation 10 , and mate preference 11 . Larval pigmentation in lepidoptera also exhibits considerable diversity and is an outstanding model system by which we can understand colour pattern evolution [12][13][14][15] .…”
mentioning
confidence: 99%
“…One exception, for a pre-mating signal, involves a pheromone QTL in the moth species Heliothis subflexa and H. virescens (Groot et al, 2013). Few studies have compared the magnitude of effect sizes within and between populations in addition to assessing whether the same QTLs are implicated, and it may be that consistent genetic effects are associated with phenotypes where large effect loci are more likely to be found, such as pheromone polymorphisms or genes influencing melanism (Wittkopp et al, 2009).…”
Section: Discussionmentioning
confidence: 99%